Severely stigmatised skin neglected tropical diseases: a protocol for social science engagement - Zaman, Shahaduz (Trans R Soc Trop Med Hyg, 2020)
More than one billion people are affected by neglected tropical diseases (NTDs) and many of these diseases are preventable. While the grouping of these conditions as NTDs has generated vast mapping, mass drug administration and surveillance programmes, there is growing evidence of gaps and weaknesses in purely biomedical approaches, and the need for responses that also recognise the social determinants of health. In order to unpack the social and political determinants of NTDs, it is important to view the problem from a social science perspective. Given this background, the Social Sciences for Severe Stigmatizing Skin Diseases (5S) Foundation has recently been established by the Centre for Global Health Research at Brighton and Sussex Medical School. The broad aim of the 5S Foundation is to incorporate social science perspectives in understanding and addressing the problems around three NTDs, namely, podoconiosis, mycetoma and scabies. This protocol paper sets out the aims and approaches of the 5S Foundation while activities such as research, public engagement, training and capacity building get underway.